Determination of shift factor for long-term life prediction of carbon/fiber epoxy composites using the time-temperature superposition principle. (1st March 2022) - Cha, Jaeho; Yoon, Sungho
Abstract: This study presents the way to determine the shift factor for predicting the long-term behavior of a carbon fiber/epoxy composite using the time-temperature superposition (TTS) principle. We conducted the multi-frequency, creep TTS, and stress relaxation TTS tests and obtained the dynamic mechanical analysis responses such as the storage modulus, creep compliance, and relaxation modulus. A shift factor determining the data movement is essential in creating the master curves. The shift factor was estimated using several methods such as the Arrhenius equation, William–Landel–Ferry equation, and manual shift method. The change in viscoelastic properties over a wide range of time was investigated by comparing the master curves to determine the most rational approach for estimating the shift factor. The master curves were obtained from the three methods based on the storage modulus. For the Arrhenius equation, the smooth master curves could not be obtained when applying a constant activation energy value. Still, using two activation energy values for the carbon fiber reinforced composite, the smooth master curves could be obtained. However, the manual shift method could get the master curves that overlap smoothly in the creep TTS and stress relaxation TTS, even without calculating activation energy values. Since the proposed procedure can estimate the long-term viscoelastic properties reasonably, the life span of the structure can be predicted at the design stage by using the master curves considering the viscoelastic properties.